A novel macroscopic computational methodology to predict the locations and orientation of solidification-cracks: Application to pulsed laser welding. (1st May 2023) - Satbhai, Ojas; Protim Neog, Suruj; Karagadde, Shyamprasad; Samajdar, Indradev; Jaya, Balila Nagamani; Kumar, Hemant; Ravikumar, R.; Mythili, R.; Ghosh, Chanchal; Dasgupta, Arup
Highlights: 3D transient model for simulation of mixed-mode or hybrid conduction-keyhole-mode pulsed laser welding with experimental verification. A novel macro-scale computational strategy for predicting in situ numerical estimations of cracking. Identification of the critical thermal parameters that govern the cracking tendency. New revelations of correlation between the crack propagation direction and the heat-lines. Abstract: The prevention of solidification cracks in critical engineering applications demands generalised predictive approaches. The first part of the manuscript reports the computation of transient temperature and flow fields using high-fidelity CFD simulations of the mixed -mode pulsed laser welding process, using iterative calculations of the volumetric heat source. The temperature field is verified by comparing the experimental and numerical weld profiles with different power-deposited-per-unit-length ϕ, which varied from 76 J/mm to 177 J/mm . The second part of this manuscript presents a novel and generalised macro-scale computational methodology which allows in situ numerical estimation of the Crack Vulnerable Index (CVI). Unlike the previous attempts, here, only the thermal characteristics, i.e., the temperature, melt flow velocity, and fluid fraction, are used to predict the locations and orientation of the cracks dynamically. The predictions agree well with the experimentally obtained findings of pulsed laser welding. The study shows that the heat-flow direction correlates closely with the crack-orientations obtained from experiments. It is experimentally observed that the cracking tendency is substantially reduced as the power-deposited-per-unit-length is increased. The bulk weld-pool solidification velocity is inversely proportional to the number-of-cracks (a measure of cracking tendency) observed in the post-solidified weldments. Further, for the case with the lower cracking tendency, the peak values of the temperature gradient and the normalized bulk weld-pool solidification velocity are ∼ 33 % and 11 % higher than the respective values for the case with the higher cracking tendency.